Tolerance towards sensor failures: an application to a double inverted pendulum - Ng, Kok Yew; Tan, Chee Pin; Akmeliawati, Rini (2006)
In this paper we present a sensor fault tolerance control scheme that is applied to a double inverted pendulum. Sensor faults will affect the system when it is used in closedloop feedback. The scheme uses a linear observer reconstruct the sensor fault and to subtract the reconstruction from the faulty sensor. The net result is then used for the closed-loop feedback. It was found that the scheme restored the performance to the fault-free scenario.